IDENTIFIKASI FASE PERTUMBUHAN TANAMAN JAGUNG MENGGUNAKAN CITRA SAR SENTINEL-1A (STUDI KASUS: KECAMATAN GERUNG, LOMBOK BARAT, NTB) - Wulandari, Baiq Arasya; Jaelani, Lalu Muhamad (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2019)
Accurate land resource information is needed to support agricultural management planning in Indonesia. Mapping regarding corn land needs to be performed because corn is one of the commodities that are highly required both for food and as a primary material for industry. Cornland mapping and identification is performed by monitoring its growth phase. By considering the area and spatial distribution of agricultural land, remote sensing becomes an efficient and accurate monitoring solution. In the tropical region, optical remote sensing is often obstructed by clouds; thus, a Synthetic Aperture Radar (SAR) sensor that has the ability to penetrate clouds and can operate in rainy weather conditions is required. For this reason,  time-series SAR Sentinel-1A radar image data recorded over Gerung District, West Lombok, in April 2018 to April 2019 were used for corn farms monitoring. The growth phase classification is carried out by the supervised classification method using the RGB: VV, VH, and cross-ratio of VV/VH composites. By analyzing the backscattering value (?°; backscatter), identification of corn stands, and the growth phase pattern of corn plants can be performed. The coefficient value of ?° of corn plant was known to be in the range of -14 to -23 dB for VH polarization and -8 to -14 dB for VV polarization with kappa accuracy of 67%.